Analisa Kelelahan Kerja dan Usulan Perbaikan dengan Menggunakan Metode Bourdon Wiersma dan New Seven Tools - Devani, Vera; Maypando, Abim Wahyu (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Employees of Public Relations work for 8 hours starting at 08.00-16.00, so it can lead to the work fatigue. Work fatigue is the condition of decreased efficiency and resilience of a person at work. Work fatigue can be caused by internal factors and external factors.The research that will be carried out is to analyze work fatigue and proposed improvements using the Bourdon Wiersma method and the New Seven Tools. Methods The method used to solve the problem is the Bourdon Wiersma method and New Seven Tools, using the Bourdon Wiersma Type Test GBT questionnaire. The respondents were 8 employees of the Public Relations division who work using computers. The aim of this research is to determine the level of speed, level of accuracy and level of consistency before and after activities, and work fatigue. Data analysis using several tools from New Seventools, namely Relationship Diagrams and Tree Diagrams. Results Based on research, the average fatigue score for speed before work was found that the average time speed for before work is 9.69 seconds with the value of speed interpretation (value 9, and WS = 14) including group B (Good), for after work was 10.05 seconds with a speed interpretation value (8.5, and WS = 13) including the CB class (Good Enough). The average accuracy for before work is 22.4 seconds with an interpretation accuracy value (value 5, and WS = -) including group R (Doubtful), for after work was 23 with an interpretation accuracy value (value 4.5, and WS = 7) included to group K (less). The average constant for before work was 11.58 with a constant interpretation value (value 5, and WS = -) including group R (Doubtful), for after work was 7.59 seconds with a constant interpretation value (value 5.5, and WS = 8) belongs to group R (Doubtful). Based on the Anova Test, the correlation value on the velocity variable was 0.937 with a very strong correlation level. The correlation value on the accuracy variable was 0.666 with a strong correlation level. The correlation value of the constant variable was 0.797 with a strong correlation level. Conclusions The main cause of fatigue in Public Relations employees is workload. The main cause of burnout in Public Relations employees is workload. The proposed improvement uses a Tree Diagram to reduce fatigue in Public Relations employees.